2021
DOI: 10.1161/circheartfailure.121.008779
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Discordance of Right- and Left-Ventricular Filling Pressures in Patients With Heart Failure by the Clinical Examination

Abstract: Background : In approximately 25% of patients with heart failure and reduced left-ventricular ejection fraction (HFrEF), right-ventricular (RV) and left-ventricular (LV) filling pressures are discordant (i.e., one is elevated while the other is not). Whether clinical assessment allows detection of this discordance is unknown. We sought to determine the agreement of clinically- versus invasively-determined patterns of ventricular congestion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…However, half of our "SubC" patient cohort showed signs of elevated central venous pressure without showing peripheral OED. Therefore, according to recent findings [14], JVD and HJR represent clinical signs with good specificity for identifying elevated RAP; when they are detectable, they it is advisable for the clinician to investigate signs of subclinical congestion through instrumental methods. By analyzing the morpho-functional parameters of the right chambers, right atrial dilation is found to be closely associated with congestion, both clinical and instrumental.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, half of our "SubC" patient cohort showed signs of elevated central venous pressure without showing peripheral OED. Therefore, according to recent findings [14], JVD and HJR represent clinical signs with good specificity for identifying elevated RAP; when they are detectable, they it is advisable for the clinician to investigate signs of subclinical congestion through instrumental methods. By analyzing the morpho-functional parameters of the right chambers, right atrial dilation is found to be closely associated with congestion, both clinical and instrumental.…”
Section: Discussionmentioning
confidence: 99%
“…PE is the cornerstone of outpatient evaluation, however it often lacks accuracy compared with other instrumental evaluations [13,14], potentially leading to under/overtreatment, especially regarding diuretic strategies [6,15]. The benefits of an integrated approach combining natriuretic peptides [16] such as the easily reproducible US signs [7,12,17] and implantable device monitoring [18] are still a matter of debate [19].…”
Section: Discussionmentioning
confidence: 99%
“…If patients continue to have end-organ dysfunction and persistently elevated PAD readings, then they should be referred to an advanced heart failure center for consideration of advanced heart failure therapies if deemed appropriate. Other situations for considering PAP sensor are in those with challenging assessment of intracardiac pressures and perfusion [32,33] and in those whose renal function and blood pressures are sensitive to GDMT or other clinical changes.…”
Section: Practical Considerationsmentioning
confidence: 99%
“…The participants with HFrEF have been described. 4 PH participants were predominantly referred for PAC by our PH Clinic. Institutional Review Board approval and informed consent were obtained.…”
mentioning
confidence: 99%
“…Our findings have clinical utility. Specifically, although bendopnea can detect an elevated PCWP in HFrEF, 4 bendopnea should not be used to assess whether PAPs are elevated in patients with a history of precapillary PH.…”
mentioning
confidence: 99%